The influence of perceived benefits, risk perception and cultural belief towards mammogram screening intention among women in Bujang Valley / Aina Nabila Mohd Radzi and Nurkhalidah Pabli - Mohd Radzi, Aina Nabila; Pabli, Nurkhalidah (2017)
Breast cancer is the most frequent diagnosed cancer among women worldwide (Globocan, 2008; World Health Organization, 2013; Soskolne, Marie & Manor, 2006). According to Globocan (2012), the estimation of breast cancer incidence rate of population is 1.7 million people. According to American Cancer Society (2015), in 2015, it is estimated 231,840 new cases of breast cancer will be diagnosed among women and approximately 40,290 women will be died from breast cancer. Breast cancer disease is the most common cancer after lung cancer when ranked by cancer occurrence in both sexes, (Ferlay, Hery, Autier & Sankaranarayanan, 2010). According to National Cancer Institute (2017), globally the total number of new cases of breast cancer diagnosed annually exceeds one million, and this figure is expected to reach 1.6 million by 2015 in United States.